Aplikasi Pemesanan Pakaian Olahraga Pada Apparel Store Berbasis Android - stevianus; eva karla (Liaison Journal of Engineering, 2022)
Many of us often neglect exercise, but we must understand how important it is for our health. The author created and developed this application to make it easier for users to learn the sportswear they need and place direct orders. The writer's research went through the following stages: (1) Performing analysis and data collection; (2) Designing applications; (3) Develop applications using Visual Studio Code and Flutter Framework as well as the Dart programming language; and (4) Test the app's functionality across three devices and users. The results of testing the app's features were positive, and everything worked. Testing on three different smartphones revealed that the program works without a hitch and has a great display. Users can access test results by filling out a questionnaire that is distributed to the user community. This survey allows users to rate the appearance, functionality and usability of the program.Keyword: Android, Sport Store, Apparel, clothes